IMPLEMENTATION OF COUNSELING GUIDELINES IN MAN 3 MEDAN - Irwansyah, Lahmuddin Lubis, Salminawati (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2019)
Abstract: This study aims to determine and analyze the problems of counseling guidance faced bystudents of MAN 3 Medan, to analyze the implementation of counseling guidance at MAN 3 Medan,to analyze the factors supporting and inhibiting counseling guidance at MAN 3 Medan,to analyzethe contributions that have resulted from the implementation of counseling guidance in MAN 3Medan. This research method uses descriptive determination method with a qualitative approach,that is, the instrument is the researcher’s own tool, data obtained from two sources, namely primaryand secondary sources. With data collection techniques through observation, interviews anddocumentation, while the data analysis technique is done by data reduction (data collection), datapresentation, and conclusions. The data validity technique is carried out with credibility, transferability,dependability and confirmability. The findings in this study, are as follows: First, the problemsfaced by students at MAN 3 Medan are not yet having the awareness to study seriously, moststudents at MAN 3 Medan have not carried out worship activities seriously, sometimes studentsshow attitude that is not polite to the teacher, shows the behavior that is generally experienced bystudents in general such as ditching, teasing friends and others and not doing homework. Secondly,the implementation of guidance and counseling at MAN 3 Medan is compiling a work programinvolving all council teachers, making work formulas related to guidance and counselingservices, mapping service areas and prioritizing in the religious field which becomes guidance andcounseling services. Third, the supporting factors for guidance and counseling services at MAN 3Medan are the existence of data instrument applications, data sets and case of conferences.Key Word: Implementation, Counseling Guidelines, Madrasah Aliyah Negeri